Fatty acids and parameters of quality in the oil of wild grapes (Vitis spp.) - Franco-Mora, O. (2015)
Mexico is one of the centers of origin of the genus Vitis. Most of the native species are in an underutilized or neglected status. Thus, this work was performed aiming the determination of the potential of Mexican native grapes as a source of plant oil. It was determined the amount of oil and its fatty acid composition in seeds of wild grapes (Vitis spp.) in fruits collected in Temascaltepec, Mexico and harvested from a cropped accession growing in Zumpahuacán, Mexico. The average content of oil in seeds was 16.7% presenting four main fatty acids, linoleic, oleic, palmitic and stearic (71.5, 17.2, 6.6 and 4.3%, respectively). In the oil obtained from Temascaltepec grapes, there were determined some oil quality indexes. Possibly, the unsaturated fatty acid content explains the index of iodine (57.9 g/100 g), soapy number (170.7 mg/g), as well as the peroxide value (30 mEq/kg). Nevertheless, the high content of unsaturated fatty acid was not related with the smoking point (211 °C), although this value might be related to the content of palmitic and stearic acid. Oil from wild grape shows similar quality parameters compared with V. vinifera seed oil, thus its culinary, agro-industrial and cosmetic potential is noted.